An Empirical Research on Audit Report Timeliness - Hendi Hendi; Riksen Sitorus (Institute of Research and Community Outreach - Petra Christian University, 2023)
Timeliness is an accounting principle that reflects economic value and relevance. Timeliness in releasing financial statements can provide relevant information and can influence decisions. This empirical study aims to examine the effect of company and audit characteristics on the timeliness of audit reports. This study uses a panel regression analysis methodology on 115 Indonesian companies listed on the Indonesia Stock Exchange from 2017-2021. This study concludes that company characteristics have a significant effect on the timeliness of audit reports. Based on the results of empirical testing, larger audit complexity, firm size, and debt-equity lead to shorter audit delays, on the other hand, negative profits and ownership concentration cause longer delays. The implications lead to more timely reporting and an appropriate decision-making process.